Psychology of the image - Forrester, Michael A. (Routledge ; Taylor & Francis, 2000)
Psychology of the Image outlines a theoretical framework bringing together the semiotic concepts developed by Charles Peirce, the sociological insights of Ervin Goffman and the psychoanalytic ideas of Jacques Lacan. Image studies in fashion, advertising, photography, film studies and psychology have been influenced by these theorists in significant ways. The framework presented helps the reader understand how these ideas relate to the study of different domains of the image: the internal imagery of dreams, external images such as the photograph and image processes which span both contex.